1994
DOI: 10.1017/s0014479700024418
|View full text |Cite
|
Sign up to set email alerts
|

RhizobiumInoculation Increases of Bean and Maize Yields in Intercrops on Farms in the Peruvian Sierra

Abstract: Nitrogen deficiency severely limits production of the bean-maize association grown by smallscale farmers in upland Peru. Sixty-four bean Rhizobium isolates were evaluated for induction of a plant growth response in pots of soil from the area and 14of the most promising strains of these were tested on farmers' fields in 13 trials over a three year period. Bean yields were increased by inoculation with at least one Rhizobium strain in seven of the trials, with increases ranging from 0.21 to 0.68 t ha" 1 . Bean y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Siame et al (1998) & Cardoso et al (2007 reported that significant increases in yield of common bean in response to N applied to maize rows were due to inefficient N 2 fixation of common bean. Other studies have shown that common bean did not respond to applied N when nodulation and fixation were good (Pineda et al 1994).…”
Section: Discussionmentioning
confidence: 89%
“…Siame et al (1998) & Cardoso et al (2007 reported that significant increases in yield of common bean in response to N applied to maize rows were due to inefficient N 2 fixation of common bean. Other studies have shown that common bean did not respond to applied N when nodulation and fixation were good (Pineda et al 1994).…”
Section: Discussionmentioning
confidence: 89%
“…This was not completely unexpected, recognizing previous research had reported benefits realized by corn when the maize-legume bicultures were collectively inoculated with symbiotic leguminous bacteria. 22,25,26 The results of this research suggest that the inoculated biculture corn indirectly benefited from either the increased nodulation of the bean as a result of an increased abundance of symbiotic nitrogen-fixing bacteria or through a change in the composition of plant-growth promoting rhizobia. Noting that the inoculated biculture bean performed equally as well when planted in monocultures, and the biculture bean appeared to recover from the reduced growth experienced under the un-inoculated condition (i.e.…”
Section: Discussionmentioning
confidence: 90%
“…The optimization of the conversion of atmospheric nitrogen to ammonia by Rhizobium has been the focus of novel sustainable intercropping practices, including the development and application of bacterial soil inoculants that promote plant productivity. [24][25][26] One study revealed a correlation between the abundance of indigenous rhizobia to the efficacy of the inoculant to promote root nodulation (i.e. low initial rhizobia population resulted in an increase in the quantity and mass of nodules).…”
Section: American Journal Of Undergraduate Researchmentioning
confidence: 99%
“…Mesoamerican strains of R. etli have also been shown to outcompete R. tropici UMR 1899, under all but acid soil conditions (Martinez and Rosenblueth 1990;Streit et al 1992;Anyango et al 1995;Hungria et al 1997). Even more surprising, significant response to inoculation of beans has been reported in the Andean center of origin of the crop (Pineda et al 1994; Instituto Nacional Autonomo de Investigaciones Agropecuarias (INIAP) 2001, unpublished data). Such specificity could be a factor in the perception of beans as weak in nodulation and nitrogen fixation, and again warrants further study.…”
Section: Discussionmentioning
confidence: 98%